Execution of strategies and safe practices in the prevention of pressure injuries (Research, Society and Development, 2020)
Pressure injury is tissue destruction and death as a result of unrelieved soft tissue compression located between bony prominence and hard surface, decreasing circulation and consequent decrease in blood, nutrients and oxygen. Nursing, as a science of care, must perform actions that do not allow the development of pressure injuries to the patient under their responsibility, with attention to those who have movement limitations. Considering this important role, this study aims to analyze the implementation of strategies and safe practices in the prevention of pressure injuries in two health units, one for urgency and emergency and the other in a hospital in a city in the center-west of São Paulo. This is a cross-sectional study with a quantitative approach, carried out with members of the Nursing team. Data collection took place in November 2019, with an instrument developed by the authors and the Pieper Knowledge Test, and were analyzed by descriptive and inferential analysis using ANOVA 1 factor. In general terms, the final result of the test showed a statistically significant difference according to professional training (p = 0.017) and the health unit in operation (p = 0.003). Even if over 60%, mid-level nursing professionals demonstrate the need to improve knowledge on this topicThe nurse and the nursing team play important roles within health institutions. This study demonstrates that knowledge, according to the nursing class, was over 60%, with greater domain by nurses. Continuing and permanent education actions aimed at the theme of pressure injury prevention must be instituted at local institutional levels, which will reflect on improving quality and safety in health care actions.